Liver transplant with controlled donors after circulatory death with normothermic regional perfusion and brain dead donors: A multicenter cohort study of transfusion, one-year graft survival and mortality. (December 2021) - Viguera, Laura; Blasi, Annabel; Reverter, Enric; Arjona, Begoña; Caballero, Marta; Chocron, Ivette; García-López, José Antonio; Gutierrez, Rosa; Martin, Maria Jesús; Pérez-Peña, Jose; Pitera, Javier; Zarragoikoetxea, Iratxe; et al.
Abstract: Background: Controlled donation after circulatory death (cDCD) has expanded the donor pool for liver transplantation (LT). However, transfusion requirements and perioperative outcomes should be elucidated. The aim of this multicenter study was to assess red blood cell (RBC) transfusions, one-year graft and patient survival after LT after cDCD with normothermic regional perfusion (NRP) compared with donors after brain death (DBD). Methods: 591 LT carried out in ten centers during 2019 were reviewed. Thromboelastometry was used to manage coagulation and blood product transfusion in all centers. Normothermic regional perfusion was the standard technique for organ recovery. Results: 447 patients received DBD and 144 cDCD with NRP. Baseline MCF Extem was lower in the cDCD group There were no differences in the percentage of patients (63% vs. 61% p = 0.69), nor in the number of RBC units transfused (4.7 (0.2) vs 5.5 (0.4) in DBD vs cDCD, p = 0.11. Twenty-six patients (6%) died during admission for LT in the DBD group compared with 3 patients (2%) in the cDCD group (p = 0.15). To overcome the bias due to a worse coagulation profile in cDCD recipients, matched samples were compared. No differences in baseline laboratory data, or in intraoperative use of RBC or one-year outcome data were observed between DBD and cDCD recipients. Conclusions: cDCD with NRP is not associated with increased RBC transfusion. No differences in graft and patient survival between cDCD and DBD were found. Donors after controlled circulatory death with NRP can increasingly be utilized with safety, improving the imbalance between organ donors and the ever-growing demand. Highlights: Donations after circulatory death (DCD) are increasingly utilized due to the imbalance between donors and recipients. Intraoperative transfusion is a known independent risk factor for patient and graft survival in liver transplantation but data comparing the source of donors is scarce. In a large cohort of liver transplants, cDCD with NRP was not associated with increased RBC transfusion. No differences in graft and patient survival between cDCD and DBD were found. Our results suggest that cDCD with NRP can safely be used, improving the imbalance between donors and recipients.